Articulating two social based informatics projects - Díaz, Francisco Javier
The Faculty of Informatics of the National University of La Plata (Buenos Aires, Argentina) is renowned among other things for its high participation in outreach projects of social character. One project is Computer literacy for disadvantaged children in society. It consists of a gradual and systematic training on ICT for children and their family environment who attend social eaters in neighborhoods on the outskirts of the city of La Plata. Since 2007, this project has been presented in different calls for outreach and volunteer projects and has been credited on all occasions and several times subsidized by university and government entities. Another project of no less importance is the EDU-WEE2 also accredited and subsidized by university and government entities, which consists of a process of assembly of PCs from components and machines donated by the community that are in disuse. This PC re-assembly has a dual purpose: first, to reduce electronic waste, and second, to contribute to the task of bridging the digital divide, as reassembled machines are donated to educational, social or health institutions that do not have computers. This article will explain how a third project based on these two was created, combining the most important characteristics and activities of each one. This pilot project was conducted during 2011 in one of the social eaters with which we have been working in the Computer Literacy Project for over 4 years. The recipients were the young working adults, recruited through a cooperative, in that social eater. In order to recover these youth from street and from addictions, the cooperative hires them to perform maintenance tasks in different non-profit civil associations. The Computer Literacy Project, along with the social eater ́s referent designed a course conceived for these young people to improve their employment opportunities. In planning the special course for these young adults, the idea of coordinating it with the project EDU-WEEE to put together a very practical course that traps the interest of the students. The resulting course was Basic PC Repair. In the process of articulation, different aspects were taken into account: cost issues, shaping common objectives, articulation of contents, integrating methodological aspects and other articulation aspects. The results obtained in this experience will be also exposed, considering the number of participants in the project, as well as the institutions involved, volunteers, activities carried out together, problems found, among others.